Understanding Of Physical Education Teachers Towards The Threat Of Dangers Of Drugs And Violence To High School Students In Depok City - Solichin; Akhmad Sobarna; Muchamad Ishak (UNIB Press, 2025)
This study aims to describe the perception of Physical Education Teachers on the Threat of Drug Abuse and Violence in High School Students in Depok City. In addition, this study also explores how teachers implement preventive measures in the learning space to overcome these problems. The focus of the study is directed at preventive efforts made by teachers in Physical Education, Sports and Health (PJOK) learning activities. This study uses a qualitative descriptive method with an exploratory approach. Data were collected through semi-structured interviews, field observations, and documentation studies. Interviews were conducted with PJOK teachers who have more than five years of experience teaching in high schools in Depok City. Data analysis was carried out through the stages of coding, categorization, and interpretation based on qualitative methods to explore the meaning and patterns of the data obtained. The results of the study indicate that PJOK teachers are aware of their important role in preventing drug abuse and violence in schools, but the implementation of preventive measures is often hampered by limited resources and operational policies. This study recommends strengthening the pedagogical competence of PJOK teachers through focused training, preparing specific operational prevention guidelines, and collaborating with schools and communities to create a safer and healthier learning environment.